2010
DOI: 10.1007/s00382-010-0974-0
|View full text |Cite
|
Sign up to set email alerts
|

The once and future pulse of Indian monsoonal climate

Abstract: We present a comprehensive assessment of the present and expected future pulse of the Indian monsoon climate based on observational and global climate model projections. The analysis supports the view that seasonal Indian monsoon rains in the latter half of the 21th century may not be materially different in abundance to that experienced today although their intensity and duration of wet and dry spells may change appreciably. Such an assessment comes with considerable uncertainty. With regard to temperature, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 55 publications
1
52
1
Order By: Relevance
“…These projections are consistent with other assessments based on CMIP3 models (see, e.g. Kumar et al, 2010).…”
Section: Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…These projections are consistent with other assessments based on CMIP3 models (see, e.g. Kumar et al, 2010).…”
Section: Temperaturesupporting
confidence: 91%
“…While most modeling studies project average annual mean increased monsoonal precipitation on decadal timescales, they also project significant increases in inter-annual and intra-seasonal variability Kumar et al 2010;May 2010;Menon, Levermann, and Schewe 2013;Sabade, Kulkarni, and Kripalani 2010;Turner and Annamalai 2012):…”
Section: Monsoonmentioning
confidence: 99%
“…Interannual monsoon variability strongly affects agricultural production, which accounts for about 22% of the Indian gross domestic product (2). Disruptions in the ISMR can lead to substantial losses in crop production that, in turn, may affect the food security of the large and growing population of India.…”
mentioning
confidence: 99%
“…However, even these small variations have important consequences for food production. Rainfall over India as a whole is known to be negatively correlated with sea surface temperature (SST) anomalies over the equatorial eastern Pacific Ocean: it tends to be enhanced during the cold years and suppressed during the warm years of the El Niño-Southern Oscillation (ENSO) cycle (2)(3)(4)(5)(6)(7)(8)(9). Rainfall during the monsoon season over India has also been linked with SST variability in the Indian Ocean: the Indian Ocean Dipole mode (10,11) and a more general warming (cooling) of the tropical Indian Ocean during El Niño (La Niña) events through the socalled atmospheric bridge that persists into the following summer (12)(13)(14).…”
mentioning
confidence: 99%
“…Atlantic climate variability and alternate ENSO indices linked to Northern Hemisphere monsoon circulation [e.g., Wang et al, 2014] might enhance the forecasting skills, but we found no statistically significant improvement with inclusion of other ENSO indices or the AMO as predictors. Changes to physical mechanisms that drive monsoon variability under a warmer climate in future [e.g., Ashfaq et al, 2009;Krishna Kumar et al, 2011] offer additional challenges to prediction.…”
Section: Discussionmentioning
confidence: 99%